Demographic aging and long-run economic growth in Germany - Christian Ochsner; Lars Other; Esther Thiel; Christopher Zuber (Sachverständigenrat zur Begutachtung der Gesamtwirtschaftlichen Entwicklung, 2024)
We study the long-run interaction between Germany's economic growth trajectory and demographic aging. Using a comprehensive dataset, we leverage the classical production function approach to estimate potential output growth between 1970 and 2070. We account for the inherent uncertainty in our projections using Bayesian estimation techniques. Overall, Germany's potential output growth up to 2070 will be low if current economic trends persist. In particular, the diminishing labor volume, coupled with sluggish total factor productivity and investment trend growth, contributes to the decline. Our results highlight the significance of demographic factors in shaping economic trajectories and the critical need for policy interventions to mitigate adverse effects. Our analysis can serve as valuable inputs for formulating long-term economic policies.
Keywords: E13; E17; E23; 330; demographic aging; production function; potential output; Germany; long-run forecast; economic growth